Increase in reflex vasoconstriction with indomethacin in patients with orthostatic hypotension and central nervous system involvement. Issue 5 (November 1984) - Imaizumi, T; Takeshita, A; Ashihara, T; Nakamura, M; Tsuji, S; Shibazaki, H
Abstract : Since indomethacin may be effective in the treatment of orthostatic hypotension, the ability of this drug to increase reflex vasoconstriction was studied in six patients with orthostatic hypotension and in five normal subjects. Reflex forearm vasoconstriction during lower body negative pressure at 20-40 mm Hg was measured before and after indomethacin 50 mg by mouth. In patients with orthostatic hypotension and central nervous system involvement indomethacin increased recumbent blood pressure, resting forearm vascular resistance, and reflex forearm vasoconstriction during lower body negative pressure. The fall in blood pressure with lower body negative pressure was not significantly inhibited by indomethacin, but mean blood pressure during lower body negative pressure was higher after than before indomethacin. Indomethacin did not alter these responses in normal subjects. The increase in reflex vasoconstriction with indomethacin may contribute to its therapeutic effects in the treatment of orthostatic hypotension.